A study of the influence of individual-level cultural value orientation on the formation of service quality expectations - Reid, Veronica (2011)
The service industry accounts for an ever-growing share of the global economy, and service aspects have become increasingly important for all goods. Since service expectations play a key role in the quality perceptions that consumers ultimately develop, it is important for service marketers to understand the nature of consumer expectations and the influences upon these expectations. Current research indicates that national culture affects service expectations, especially the information sources that consumers use and their opinion seeking propensity. However, cross-cultural expectation formation is a particularly under-researched area and researchers using national culture as an explanatory variable tend not to develop rigorous conceptual models clearly explicating how culture is meant to affect the consumer behaviour being examined. This research examines cross-cultural expectation formation and thus contributes to increasing academic understanding and improving marketers’ ability to manage the expectation formation process across cultures. Specifically, this research sought to empirically test the influence of individual-level cultural dimensions on the relative importance of the key antecedents of consumers’ expectations of service quality. A conceptual framework linking cultural factors to the formation of expectations was developed and empirically tested in a multicultural setting to explore similarities and differences between customers with significantly different cultural values.